PENGARUH KARAKTER EKSEKUTIF, KARAKTERISTIK PERUSAHAAN, DAN PENGUNGKAPAN TANGGUNG JAWAB SOSIAL PERUSAHAAN TERHADAP PENGHINDARAN PAJAK (Studi Empiris Perusahaan Pertambangan yang Terdaftar di BEI 2011-2013) - Dewi, Nurrahma; Nasir, Azwir; ', Hariadi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2016)
This Study aims to identify and analyze the effect of character, company characteristic, and corporate social responsibility to tax avoidance. The executive character variable is proxied by corporate risk, meanwhile company characteristic variable is proxied by company size, multinational company, leverage, capital intensity ratio. Then at least, corporate social responsibility disclosure variable. This study uses secondary data with 57 mining companies sample listed in Indonesia Stock Exchange for three periods (2011-2013). The sampling technique used is purposive sampling analysis. The analytical method used is multiple regression by using spss 1.7. Based on the results of hypothesis testing found that corporate risk is as proxy of executive character, multinational company and leverage are as proxy of characteristic company, and corporate social responsibility disclosure affect and significant tax avoidance. Meanwhile company size and capital intensity ratio are as proxy characteristic company haven’t affect and haven’t significant tax avoidance.Keyword : Executive Character, Company Characteristic, Corporate Social Responsibility Disclosure, and Tax Avoidance.